Correlations between Traditional and Nontraditional Indicators of Adiposity, Inflammation, and Monocyte Subtypes in Patients with Stable Coronary Artery Disease - Silvia Bueno Garofallo; Vera Lucia Portal; Melissa Medeiros Markoski; Lucinara Dadda Dias; Alexandre Schaan de Quadrosa; Aline Marcadenti (Journal of Obesity)
Background. Recruitment of monocytes and low-grade inflammation process are both involved in obesity and in atherosclerosis. Thus, the aim of this study was to evaluate the correlation among indicators of adiposity, monocyte subtypes, and inflammatory markers in patients with stable coronary artery disease (CAD). Methods. This was a cross-sectional study including 97 patients with stable CAD aged >40 years. Traditional anthropometric indicators of adiposity (body mass index (BMI); waist, hip, and neck circumferences; and waist-hip ratio) and nontraditional anthropometric indicators of adiposity (lipid accumulation product index (LAP), visceral adiposity index (VAI), and deep-abdominal-adipose-tissue index (DAAT)) were determined. Immunoprecipitation, turbidimetry, coagulometric method, and CBA were used for the evaluation of inflammatory markers (hs-CRP, IL-2, IL-4, IL-6, IL-10, and INF-γ). Monocyte subtypes were identified by flow cytometry and defined as CD14++ CD16− (Mon1), CD14++ CD16+ (Mon2), and CD14+ CD16++ (Mon3). Pearson’s correlation coefficient and adjusted partial correlation were calculated. Results. Monocyte subtypes were correlated with inflammation regardless of nutritional status according to BMI. In overweight individuals, LAP was correlated with IL-4 and fibrinogen (P<0.01 and P<0.05, respectively) and VAI with IL-4 (P<0.05). In obese patients, the BMI, waist, neck, and hip circumferences, and DAAT were correlated with IL-6 (P<0.05), regardless of age and sex. The hip circumference was correlated positively with Mon1 (r = 0.40, P=0.007) and negatively with Mon3 (r = −0.35, P=0.02) in obese subjects. Conclusion. Monocyte subtypes are correlated with inflammation in patients with stable CAD independently of BMI, whereas traditional and nontraditional indicators of adiposity are correlated differently with inflammatory markers and monocytes, according to the nutritional status.